EVALUASI KESUKSESAN SISTEM PELATIHAN JARAK JAUH PADA BALAI DIKLAT KEUANGAN MAKASSAR DI MASA PANDEMI COVID-19 - Azwar Iskandar (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2022)
This study aims to measure the success of the implementation of distance learning systems in the Financial Education and Training Agency of Makassar during the pandemic. This study used data obtained from respondents through questionnaires and quantitative approaches through component or variant-based of Structural Equation Modelling (SEM) techniques with Partial Least Square (PLS). The results show that in general the distance learning system has not fully run well and successfully based on indicators or approach of DeLone and McLean model. The system quality affects user satisfaction and user satisfaction also affects the net benefits. Meanwhile, the information quality and service quality has no effect on user satisfaction. Financial Education and Training Agency of Makassar is expected to improve the quality of information and quality of services in order to improve the satisfaction of training participants that will have an impact on the achievement of learning outcomes.